خطاب الإرهاب وتبعاته على النص الديني دراسة نصية سياقية۔: The frame of terrorism discourse and its consequences on the Islam Low text: textual and context study (Khairulummah, 2023)
The terrorism has been a source of concern for human societies, indeed the non-Muslims participate in manufacture of terrorism as some Muslim participate,  for this reason, the groups of terrorism has been developed in the name of Islam and Islam is innocent of them, these groups are kill and destroy, and their terrors operations are justified by religious texts. This paper attempts to study how terrorists build their personal understanding on some verses in the holy Qur’an to justify what are doing against humanities and its civilizations, and also paper analyses some Qur’an and Hadis texts that terrorist depend on it, The study adopts the descriptive and normative methods to find the research results.
Keywords: Discourse, terrorism, consequences, language of text, Islamic Law.